Congenital myasthenic syndrome due to mutations in MUSK suggests that the level of MuSK phosphorylation is crucial for governing synaptic structure. Issue 3 (25th November 2019) - Rodríguez Cruz, Pedro M.; Cossins, Judith; Cheung, Jonathan; Maxwell, Susan; Jayawant, Sandeep; Herbst, Ruth; Waithe, Dominic; Kornev, Alexandr P.; Palace, Jacqueline; Beeson, David
Abstract: MUSK encodes the muscle‐specific receptor tyrosine kinase (MuSK), a key component of the agrin‐LRP4‐MuSK‐DOK7 signaling pathway, which is essential for the formation and maintenance of highly specialized synapses between motor neurons and muscle fibers. We report a patient with severe early‐onset congenital myasthenic syndrome and two novel missense mutations in MUSK (p.C317R and p.A617V). Functional studies show that MUSK p.C317R, located at the frizzled‐like cysteine‐rich domain of MuSK, disrupts an integral part of MuSK architecture resulting in ablated MuSK phosphorylation and acetylcholine receptor (AChR) cluster formation. MUSK p.A617V, located at the kinase domain of MuSK, enhances MuSK phosphorylation resulting in anomalous AChR cluster formation. The identification and evidence for pathogenicity of MUSK mutations supported the initiation of treatment with β2‐adrenergic agonists with a dramatic improvement of muscle strength in the patient. This work suggests uncharacterized mechanisms in which control of the precise level of MuSK phosphorylation is crucial in governing synaptic structure. Abstract : We report a patient with severe early‐onset congenital myasthenic syndrome and two novel missense mutations in the muscle‐specific receptor tyrosine kinase ( MUSK ; p.C317R and p.A617V). Functional studies show that p.C317R, located at the frizzled‐like cysteine‐rich domain of MuSK, disrupts an integral part of MuSK architecture resulting in ablated MuSK phosphorylation and acetylcholine receptor (AChR) cluster formation. The p.A617V substitution, located at the kinase domain of MuSK, enhances MuSK phosphorylation resulting in anomalous AChR cluster formation. This work suggests uncharacterized mechanisms in which control of the precise level of MuSK phosphorylation is crucial in governing synaptic structure.